PENTINGNYA MENYEKOLAHKAN ANAK KATOLIK DI SEKOLAH KATOLIK DALAM TERANG GRAVISSIMUM EDUCATIONIS - Albert I Ketut Deni Wijaya; Yohana Inez Purwanto (Bahasa Indonesia, 2018)
Catholic parents are the first and primary teacher for their children, that precious task could not be replaced by anyone else. Teachers in the school could not be said as first and primary educators, because their task is just to help parents to deepen their children's knowledge. Catholic parents should choose opportune school to develop children's faith, because this time many parents are busy with their work until they forget with this main task to teach their children about faith. Catholic school is a right option for developing children's faith so children are more believe in Jesus Christ. The result of this research in general, showed that Catholic parents reveal indeed very important of Catholic children schooled at Catholic School. The Catholic parents want the faith of Catholicism owned by children can be nurtured from an early age to adulthood later. Catholic parents really aware of the limitations in fostering the faith of children. Therefore, some Catholic parents prefer to schooled their children in Catholic school in accordance with the mandate of Gravissimum Educationis.